2017
DOI: 10.1155/2017/5247305
|View full text |Cite
|
Sign up to set email alerts
|

Main Controlling Factor of Polymer-Surfactant Flooding to Improve Recovery in Heterogeneous Reservoir

Abstract: This study aims to analyze the influence of viscosity and interfacial tension (IFT) on the recovery in heterogeneous reservoir and determines the main controlling factors of the polymer-surfactant (SP) flooding. The influence of the salinity and shearing action on the polymer viscosity and effects of the surfactant concentration on the IFT and emulsion behavior between chemical agent and oil were studied through the static and flooding experiments. The results show that increasing the concentration of polymer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Therefore, the viscosity of the surfactant has to be optimized. However, it is reported that high viscosity surfactant is required to reduce the oil-water mobility ratio and enhance oil recovery [12]. Fig.…”
Section: Surfactants Viscosity Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the viscosity of the surfactant has to be optimized. However, it is reported that high viscosity surfactant is required to reduce the oil-water mobility ratio and enhance oil recovery [12]. Fig.…”
Section: Surfactants Viscosity Testmentioning
confidence: 99%
“…Therefore, this polymer can be used in the EOR process. Yin and Zhao [12] studied the effect of viscosity and face stress for oil uptake in heterogeneous reservoirs and determined controlling factors on surfactant-polymer (SP) flooding. The results showed that the higher the polymer concentration would increase the viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that a high surfactant viscosity is needed in the EOR process. Surfactants with high viscosity can enhance or increase oil recovery due to their ability to reduce oil-water mobility [14,15]. Even though a viscous surfactant can enhance or increase the oil recovery in the EOR process, it may block the pore of rock [3].…”
Section: Viscosity Test Of Surfactantsmentioning
confidence: 99%
“…However, if the viscosity of the surfactant is too high, it can block the reservoir; conversely, if the viscosity of the surfactant is too low, mobility is not appropriate [14]. Yin and Zhao [15] have studied the effect of viscosity and interfacial tension on oil recovery in the heterogeneous reservoir and determined the main controlling factors of the polymer-surfactant (SP) flooding. They reported that a higher polymer concentration could increase the surfactant viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…Flory discussed the possibility of HBP syntheses by polycondensation of the AB x -type monomer, to which attention was not paid at the time (Flory, 1941;Flory, 1952). The studies on the topic have thrived since 1990s, and their applications have been extended to enhanced oil recovery (Algharaib et al, 2014;Sun et al, 2016;Yin and Zhao, 2017). Addition of HBPs leads to greater oil recovery than conventional polymers in core flooding experiments (Luo et al, 2019;Jianbo et al, 2020;Chen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%